Psychological Status Associated With Low Quality of Life in School-Age Children With Neurodevelopmental Disorders During COVID-19 Stay-At-Home Period - Ueda, Riyo; Okada, Takashi; Kita, Yosuke; Ozawa, Yuri; Inoue, Hisami; Shioda, Mutsuki; Kono, Yoshimi; Kono, Chika; Nakamura, Yukiko; Amemiya, Kaoru; Ito, Ai; Sugiura, Nobuko; et al. (Frontiers in Psychiatry, 2021)
Background: This study seeks to ascertain how the COVID-19 stay-at-home period has affected the quality of life (QOL) of children with neurodevelopmental disorders (NDDs) who had experienced sleep schedules alteration and clarify what psychological status predicted low QOL in children with and without altered sleep patterns. Materials and Methods: Study participants were 86 children between 8 and 17 years of age (mean age, 11.7 years; 70 boys, 16 girls; mean intellectual quotient, 83.6). QOL was evaluated using the self-assessment KINDLR. Participants answered questions regarding depression and anxiety on a visual analog scale (VAS) for temporary mood. Their parents answered questionnaires regarding their maladaptive behaviors and differences in sleep patterns before and during the COVID-19 pandemic. The student’s t-test was performed to examine the presence or absence of sleep changes in the children, which affected QOL, temporary mood, and maladaptive behaviors. Multiple or simple linear regression analyses were also performed to identify the psychogenic factors that significantly affected decreased QOL for each group with and without changes in sleep schedule. Results: During the COVID-19 stay-at-home period, 46.5% of participants experienced changes in sleep patterns. These changes were associated with decreased QOL as well as internalized symptoms. The decreased QOL of children with sleep patterns changed was predicted by a high level of depression. In addition, low QOL in children with unchanged sleep patterns was predicted by a high level of depression and low current mood status. Conclusions: Almost half of the participants experienced a poor sleep schedule during the stay-at-home period. These alterations in sleep patterns were associated with a low QOL. The QOL of children with a stable life schedule was affected not only by depressive tendencies but also temporary moods. Therefore, they need to live a fulfilling life to maintain their QOL. However, the QOL of children with poor sleep patterns was affected only by depressive tendencies. Hence, clinicians need to ensure that children with NDDs are well diagnosed with depression and treated for sleep problems.